Validation of the Spartan RXCYP2C19 Genotyping Assay Utilizing Blood Samples - Brittney H. Davis; Gina DeFrank; Nita A. Limdi; Shuko Harada (Wiley, 2020)
The antiplatelet agent clopidogrel, a prodrug that requires bioactivation through the cytochrome P450 2C19 (CYP2C19) enzyme, is commonly prescribed post‐percutaneous coronary intervention (PCI). Genetic variation in CYP2C19 contributes to individual variability in clopidogrel response, and can lead to adverse cardiovascular events. Incorporating CYP2C19 testing during routine clinical care helps identify high‐risk patients, and provides the opportunity for pharmacotherapeutic interventions in the early post‐PCI period. The Spartan RX CYP2C19 System has emerged as an optimal genotyping assay for use in clinical care due to ease of use, utilization of buccal swabs, and rapid turnaround time. However, workflow constraints related to sample collection and processing, storage, time, and personnel were encountered when integrating testing into clinical care. To improve clinical workflow and successfully implement CYP2C19 genotyping at our institution, we validated the Spartan RX System to return genotype utilizing blood samples. Our Molecular Diagnostic Laboratory tested 26 known reference materials and both blood and buccal swab samples from 23 patients and volunteers using the Spartan RX Assay. Genotype results were 100% concordant between DNA from blood and buccal swabs for all patients or volunteers, and consistent with expected results for the 26 reference materials. For reproducibility, three samples were tested in at least four separate runs, with all resulting genotypes in agreement between runs. Post‐validation, the laboratory began offering CYP2C19 testing during clinical care. DNA extracted from blood can serve as a genomic DNA source for the Spartan RX Assay. Alteration of the methodology allowed for clinical implementation to support genotype‐guided therapy.